Therapeutic protein–drug interaction assessment for daclizumab high‐yield process in patients with multiple sclerosis using a cocktail approach - Tran, Jonathan Q. (Br J Clin Pharmacol, 2016)
AIMS: To characterize the potential effect of daclizumab high‐yield process (DAC HYP), a monoclonal antibody that blocks the high‐affinity interleukin‐2 receptors for treatment of multiple sclerosis, on activity of cytochrome P450 (CYP) enzymes. METHODS: Twenty patients with multiple sclerosis received an oral cocktail of probe substrates of CYP1A2 (caffeine 200 mg), CYP2C9 (warfarin 10 mg/vitamin K 10 mg), CYP2C19 (omeprazole 40 mg), CYP2D6 (dextromethorphan 30 mg) and CYP3A (midazolam 5 mg) on two sequential occasions: 7 days before and 7 days after subcutaneous administration of DAC HYP 150 mg every 4 weeks for three doses. Serial pharmacokinetic blood samples up to 96 h post dose and 12‐h urine samples were collected on both occasions. Area under the curve (AUC) for caffeine, S‐warfarin, omeprazole and midazolam, and urine dextromethorphan to dextrorphan ratio were calculated. Statistical analyses were conducted on log‐transformed parameters using a linear mixed‐effects model. RESULTS: The 90% confidence intervals (CIs) for the geometric mean ratio (probe substrate with DAC HYP/probe substrate alone) for caffeine AUC from 0–12 h (0.93–1.15), S‐warfarin AUC from 0 to infinity (AUC[0–inf]) (0.95–1.06), omeprazole AUC(0–inf) (0.88–1.13) and midazolam AUC(0–inf) (0.89–1.15) were within the no‐effect boundary of 0.80–1.25. The geometric mean ratio for urine dextromethorphan to dextrorphan ratio was 1.01, with the 90% CI (0.76–1.34) extending slightly outside the no‐effect boundary, likely due to high variability with urine collections and CYP2D6 activity. CONCLUSIONS: DAC HYP treatment in patients with multiple sclerosis had no effect on CYP 1A2, 2C9, 2C19, 2D6 and 3A activity.